Analysis of Da’wah Messages in Kadam Sidik Lectures on YouTube: (Study on the Most Realistic Hijrah Strategy Video) - Nurfirdaus, Muhammad Naufal (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
This study aims to analyze the da’wah message conveyed by Kadam Sidik in his lecture video on YouTube entitled